The amygdaloid body of the family Delphinidae: a morphological study of its central nucleus through calbindin-D28k - Sacchini, Simona; Bombardi, Cristiano; Arbelo, Manuel; Herráez, Pedro (Frontiers in Neuroanatomy, 2024)
Introduction The amygdala is a noticeable bilateral structure in the medial temporal lobe and it is composed of at least 13 different nuclei and cortical areas, subdivided into the deep nuclei, the superficial nuclei, and the remaining nuclei which contain the central nucleus (CeA). CeA mediates the behavioral and physiological responses associated with fear and anxiety through pituitary-adrenal responses by modulating the liberation of the hypothalamic Corticotropin Releasing Factor/Hormone. Methods Five dolphins of three different species, belonging to the family Delphinidae (three striped dolphins, one common dolphin, and one Atlantic spotted dolphin), were used for this study. For a precise overview of the CeA’s structure, thionine staining and the immunoperoxidase method using calbindin D-28k were employed. Results CeA extended mainly dorsal to the lateral nucleus and ventral to the striatum. It was medial to the internal capsule and lateral to the optic tract and the medial nucleus of the amygdala. Discussion The dolphin amygdaloid complex resembles that of primates, including the subdivision, volume, and location of the CeA.